Report on the debate regarding EU cash payment limitations. Issue 1 (2nd January 2018) - Passas, Nikos
Abstract : Purpose: Response to suggestion that EU-wide cash payment limits would assist in the control of terrorism finance and money laundering. Design/methodology/approach: Desk review and interviews Findings: The inception impact assessment (IIA) is ill-conceived, not grounded on firm empirical evidence and harmful to both crime control and the legitimate interests and rights of the EU citizens. The action under discussion is presented as a measure against terrorism finance, serious crime and tax evasion. The problem is that these criminal acts correspond to very different methods, volumes, perpetrators, causes and control challenges. Cash payment limitations (CPLs) are nowhere near a panacea that can address all of them and cannot make any of them go away magically. Even when each of these crime challenges are considered on their own, the empirical linkage of CPLs to effective controls is not there. The evidence from EU countries with CPLs in place shows higher levels of informal economy, corruption, tax evasion and terrorism risks than those without. There is substantial evidence of non-cash, very serious and organized crime, while the amounts needed and used by terrorists in Europe are usually very small in cash transactions, way below the thresholds under consideration. In fact, determined offenders will shift to other methods and become more sophisticated, posing new problems to controllers. Displacement and incentives for better-organized crime may well be the main products of such measures. Originality/value: It counters the argument that the cash payment limits can help reduce serious crime, while pointing to several adverse consequences on legitimate interests and human rights.